2011
DOI: 10.1021/la104449y
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific Adsorption of Charged Quantum Dots on Supported Zwitterionic Lipid Bilayers: Real-Time Monitoring by Quartz Crystal Microbalance with Dissipation

Abstract: Understanding how the composition and environmental conditions of membranes influence their interactions with guest species is central to cell biology and biomedicine. We herein study the nonspecific adsorption of charged quantum dots (QDs) onto a supported zwitterionic lipid bilayer by using quartz crystal microbalance with dissipation (QCM-D). It is demonstrated that (1) the adsorption of charged QDs is charge-dependent in a way similar to but much stronger than that of the capping molecules by reason of siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 45 publications
5
61
0
Order By: Relevance
“…A quartz crystal microbalance (QCM) with dissipation monitoring can be used for real-time monitoring of nanoparticle-lipid membrane interactions. 74 Fluorescence microscopy, 65,75 fluorescence spectroscopy, 68 fluorescence correlation spectroscopy (FCS), 73 Föster resonance energy transfer, 73,76 NMR 77 and liposomal leakage assay 78 have all been used to study the biophysical changes and disruptions of model lipid membranes or liposomes by nanoparticles.…”
Section: Nanoparticle-biomolecule Interactionsmentioning
confidence: 99%
“…A quartz crystal microbalance (QCM) with dissipation monitoring can be used for real-time monitoring of nanoparticle-lipid membrane interactions. 74 Fluorescence microscopy, 65,75 fluorescence spectroscopy, 68 fluorescence correlation spectroscopy (FCS), 73 Föster resonance energy transfer, 73,76 NMR 77 and liposomal leakage assay 78 have all been used to study the biophysical changes and disruptions of model lipid membranes or liposomes by nanoparticles.…”
Section: Nanoparticle-biomolecule Interactionsmentioning
confidence: 99%
“…A number of QDs such as CdSe, 21 CdSe/ZnS, 22,23 CdSe/CdZnS, 16 CdTe, 17,24 and carbon 25 have been embedded into the hydrophobic tail region of liposomes without significantly compromising the liposome structure. Nonspecific QD adsorption to pre-formed supported lipid bilayers (SLBs) 26 and polyelectrolyte multilayers (PEMs) 27 has also been previously studied. However, the formation and structure of QD-embedded SLBs via the fusion of QD-endowed liposomes has not been reported, which is the focus of the current study.…”
Section: 20mentioning
confidence: 99%
“…This hypothesis is supported by the work described by Zhang et al, where the authors demonstrated that adsorption between charged QDs and zwitterionic membranes can be favored by charges, which in turn can be controlled by the environmental pH and by the membrane and QD compositions. 47 The authors have shown the existence of an "adsorption window" that can govern the binding (or not) of QDs to lipids when these species display opposite charges. In this way, interactions between the negative carboxyl-coated QDs and cationic membranes (liposomes or cells) may well explain the co-localized pattern observed in Fig.…”
Section: Discussionmentioning
confidence: 99%